Pelatihan Berpikir Positif untuk meningkatkan kepercayaan diri Pada Mahasiswa Generasi Z - Muzaki, Muhammad Farhan Ni'am; Malahati, Fildzah (Neolectura, 2025)
This study aims to examine the effectiveness of positive thinking training in enhancing self-confidence among Generation Z students. Generation Z is known as the generation that lives in the digital era, where face-to-face interactions tend to decrease due to reliance on technology and social media. This research employed an experimental method with a pre-test and post-test design involving experimental and control groups. The research sample consisted of 60 students selected through purposive sampling. The instrument used was a self-confidence scale. Statistical analysis results indicate that positive thinking training significantly increased self-confidence in the experimental group compared to the control group. The findings highlight the importance of developing positive thinking training programs for students to improve their self-confidence in addressing social and academic challenges